Environmental, Social, and Governance to Firm Value: Profitability as a Moderating Variable - Pardamean, Risky Jhonatan; Gunawan, Yuliana (Universitas Kristen Maranatha, 2025)
Purpose – This study aims to explore in depth analyze aspects related to environmental, social responsibility, and governance (ESG) on firm value where profitability is considered as a moderating element in analytical models. Design/Methodology/Approach – A quantitative approach was employed in this study using Moderated Regression Analysis (MRA). The sample was selected through a purposive sampling technique, resulting in 210 firm-year observations from the 2019–2023 period that met specific criteria, such as having ESG scores and published sustainability reports. Findings – The results demonstrate that ESG scores do not have a positive impact on firm value, while profitability projected through Return on Assets (ROA) has a positive impact on firm value. However, profitability does not act as a moderator in the relationship between ESG and firm value. Research limitations/Implications – These findings imply that while ESG holds strategic value in sustainability strategies, its influence on company valuation Indonesian firms is limited. The results of this study have the implication that firms should put more emphasis on enhancing profitability as a strategy to boost firm value. The limitations of the study lie in the small research sample that qualifies as research samples. Keywords: ESG, Firm Value, Profitability, Moderation, Sustainability